2010
DOI: 10.2337/db10-1198
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Hemoglobin and the Risk of Kidney Disease and Retinopathy in Adults With and Without Diabetes

Abstract: OBJECTIVEGlycated hemoglobin was recently recommended for use as a diagnostic test for diabetes. We examined the association between 2010 American Diabetes Association diagnostic cut points for glycated hemoglobin and microvascular outcomes (chronic kidney disease, end-stage renal disease [ESRD], and retinopathy) and formally tested for the presence of risk thresholds in the relationships of glycated hemoglobin with these outcomes.RESEARCH DESIGN AND METHODSProspective cohort and cross-sectional analyses of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 35 publications
7
102
0
3
Order By: Relevance
“…Longitudinal studies did not find prediabetes to be an independent risk factor for albuminuria or incident CKD, defined as an estimated GFR < 60 ml/min/1.73 m 2 . [6][7][8][9][10][11] If prediabetes is a causal factor in the development of kidney disease, this condition would represent a window of opportunity to treat kidney damage at an early and reversible stage.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies did not find prediabetes to be an independent risk factor for albuminuria or incident CKD, defined as an estimated GFR < 60 ml/min/1.73 m 2 . [6][7][8][9][10][11] If prediabetes is a causal factor in the development of kidney disease, this condition would represent a window of opportunity to treat kidney damage at an early and reversible stage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk of developing diabetesrelated complications rises steadily when glycated hemoglobin (HbA 1c ) values are in excess of 6.5% (48 mmol/mol) (4,5), an HbA 1c of ,7% (,53 mmol/mol) is generally considered a target goal for diabetes management (6). In truth, it is now widely recognized that individualizing the HbA 1c goal for each patient is critically important, especially when the presence of comorbidities necessitates less stringent targets (6).…”
Section: Achievement Of Hba 1c Goals In the Real Worldmentioning
confidence: 99%
“…A large cohort study reported a strong association between fasting plasma glucose (FPG) level and renal function even in subjects without DM (6). Furthermore, hypertension and/or dyslipidemia frequently coexist with CKD, which are often associated with marked renal impairment (7,8).…”
Section: Introductionmentioning
confidence: 99%